Multicultural Education Islamic Perspective in Building Intercultural Tolerance: A Systematic Literature Review with a PRISMA Approach - Siti Kholida; Mujamil Qomar; Syamsun Ni’am; Adiyono (Didaktika: Jurnal Kependidikan, 2025)
This research investigates the challenges and opportunities in implementing multicultural education within Islamic educational institutions, with a particular focus on integrating inclusivity and diversity into the learning process. The problem addressed in this study is the limited competence of teachers in applying multicultural values, the lack of contextual teaching materials, and the persistence of exclusive cultural resistance among certain local communities. The objective of the research is to identify systemic barriers, analyze their impact on students’ attitudes, and propose practical solutions for fostering a more inclusive educational environment. The study employs a qualitative descriptive method, combining literature review, document analysis, and interviews with teachers and students to capture both theoretical and empirical perspectives. The results reveal that despite existing good practices, significant obstacles remain, such as stereotypes among students due to minimal intercultural interaction and weak policy support for multicultural education. However, the study also highlights effective strategies, including teacher training programs, curriculum contextualization, dialogical engagement with local culture, and the creation of inclusive school environments. These findings underscore the need for comprehensive policy reform and sustainable teacher development to strengthen multicultural integration in Islamic education. The research contributes to the discourse on educational reform by offering practical pathways for promoting harmony and respect for diversity within Islamic schooling contexts.